Penyebab Perilaku Cybersex dan Dampaknya pada Perilaku Mahasiswa (Studi Kualitatif di Kabupaten Jember) - Huwaidah, Rizka; Rokhmah, Dewi; Ririanty, Mury (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2020)
Cybersex occurs when someone uses the internet as a medium of interaction to get sexual satisfaction. The triggers for cybersex behaviour can consist of the individual himself or a supportive environment. The purpose of this study was to analyze the causes of cybersex behaviour and its impact on student behaviour. This research is qualitative research with a case study approach. The results showed that cybersex was caused by curiosity, fun, peer influence, exposure to pornographic content advertisements, stimulation of taboo conversations from interlocutors, easy internet access, and the influence of adult films. The pre-marital sex behaviour carried out by the informants consisted of kissing, necking, petting, and intercourse. The impact felt by informants on cybersex behaviour was a disruption of sleep time and informants tended to stay up late at night due to cybersex. In addition, if they did not do cybersex, informants felt confused, felt that something was missing, and were anxious.